Daylight In Office Buildings In Malaysia: A Pilot Study On Occupant's Satisfaction And Luminous Environment - Elina Mohd Husini; Fadli Arabi; Remaz Ossen Dilshan; Mohd Zin Kandar; Norhaini Mat Lajis (Common Ground Research Networks, 2024)
Spaces and Flows: An International Journal of Urban and ExtraUrban Studies 3 (1): 1-20